2017
DOI: 10.1002/hbm.23698
|View full text |Cite
|
Sign up to set email alerts
|

Cross-population myelination covariance of human cerebral cortex

Abstract: Cross-population covariance of brain morphometric quantities provides a measure of inter-areal connectivity, as it is believed to be determined by the coordinated neurodevelopment of connected brain regions. Although useful, structural covariance analysis predominantly employed bulky morphological measures with mixed compartments, whereas studies of the structural covariance of any specific subdivisions like myelin are rare. Characterizing myelination covariance is of interest, as it will reveal connectivity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
(113 reference statements)
1
16
1
Order By: Relevance
“…Glasser and colleagues reported that T1‐weighted (T1w)/T2‐weighted (T2w) ratio value could reflect cortical myelination (Glasser & Van Essen, ). Evidence shows that this method can precisely estimate cortical myelination: (a) Virtual boundaries of brain regions generated based on T1w/T2w ratio were well aligned with results in prior anatomical and functional brain study (Glasser & Van Essen, ); (b) T1w/T2w ratio had similar cortical distribution compared to signal density pattern in neurite imaging (Fukutomi et al, ); (c) abnormal myelination of WM revealed by this method was highly consistent with the DTI results in patients with multiple sclerosis (Nakamura, Chen, Ontaneda, Fox, & Trapp, ); (d) structural covariance networks generated based on T1w/T2w ratio corresponded to functional brain network (Ma & Zhang, ). Hagiwara et al also demonstrated that the correspondence between T1w/T2w ratio and myelin water fraction was strong across the gray matter (Hagiwara et al, ).…”
Section: Introductionsupporting
confidence: 73%
“…Glasser and colleagues reported that T1‐weighted (T1w)/T2‐weighted (T2w) ratio value could reflect cortical myelination (Glasser & Van Essen, ). Evidence shows that this method can precisely estimate cortical myelination: (a) Virtual boundaries of brain regions generated based on T1w/T2w ratio were well aligned with results in prior anatomical and functional brain study (Glasser & Van Essen, ); (b) T1w/T2w ratio had similar cortical distribution compared to signal density pattern in neurite imaging (Fukutomi et al, ); (c) abnormal myelination of WM revealed by this method was highly consistent with the DTI results in patients with multiple sclerosis (Nakamura, Chen, Ontaneda, Fox, & Trapp, ); (d) structural covariance networks generated based on T1w/T2w ratio corresponded to functional brain network (Ma & Zhang, ). Hagiwara et al also demonstrated that the correspondence between T1w/T2w ratio and myelin water fraction was strong across the gray matter (Hagiwara et al, ).…”
Section: Introductionsupporting
confidence: 73%
“…T 1 w/T 2 w ratio is another approach for assessing myelin content in the cortical gray matter, originally developed to map myeloarchitecturally distinct cortical regions for parcellation of cerebral cortex, thus providing a connectivity measurement 33 , 34 . Pixel intensity on T 1 w and T 2 w images is assumed to be directly and inversely proportional to myelin contrast, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The use of T1-w/T2-w ratio in measuring structural covariance has been shown to produce brain organization similar to that of other structural measures and is validated as reproducible in adults and children (21,22). Our data support the use of T1-w/T2-w ratio to measure myelin covariance -our structural covariance networks demonstrated organization as well as high and symmetric intra-hemispheric connectivity in both children and adults, consistent with our previous study using MT (15).…”
Section: Discussionmentioning
confidence: 97%
“…An alternative approach is to take the ratio of two commonly acquired images, T1-weighted (T1-w) and T2-weighted (T2-w) to form a voxel-wise map of myelin estimates (17)(18)(19)(20). The concordance between MT and the T1-w/T2-w ratio appears to be high in both the white and grey matter (21), and has been shown as a valid and reproducible measure to use when examining structural covariance (22) . Moreover, as the two elements required for this technique are often routinely acquired, there are opportunities for retrospective analyses of large datasets.…”
Section: The Relation Between Functional Connectivity and Structural mentioning
confidence: 99%